2011
DOI: 10.1186/1475-2875-10-140
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of determinants on coverage of intermittent preventive treatment of malaria during pregnancy in the Kilombero Valley, Tanzania

Abstract: BackgroundIntermittent preventive treatment during pregnancy (IPTp) at routine antenatal care (ANC) clinics is an important and efficacious intervention to reduce adverse health outcomes of malaria infections during pregnancy. However, coverage for the recommended two IPTp doses is still far below the 80% target in Tanzania. This paper investigates the combined impact of pregnant women's timing of ANC attendance, health workers' IPTp delivery and different delivery schedules of national IPTp guidelines on IPTp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 43 publications
9
38
0
Order By: Relevance
“…Consistent with other studies, our findings suggest that health provider practices rather than women's ANC attendance are primarily responsible for the ineffectiveness of the IPTp strategy in this setting [18,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with other studies, our findings suggest that health provider practices rather than women's ANC attendance are primarily responsible for the ineffectiveness of the IPTp strategy in this setting [18,[21][22][23][24].…”
Section: Discussionsupporting
confidence: 89%
“…Stock outs of SP, absence of cups and clean drinking water for taking SP by DOT [17], unclear guidelines [21] or confusion among health workers regarding the guidelines [24] and other related health facility factors [15,25] are factors which hamper delivery of IPTp.…”
Section: Discussionmentioning
confidence: 99%
“…Further, if many health professional students have to be present during service provision, a different culture for how to approach the women could be encouraged. In other settings, it has been suggested that improved quality of care can be achieved by in-service training and improved supportive structures at managing levels [10, 41, 47, 52]. …”
Section: Discussionmentioning
confidence: 99%
“…Interest in this topic was triggered by data from qualitative and quantitative studies on women's access to antenatal care (ANC) and malaria prophylaxis in rural south-eastern Tanzania (Gross et al 2011(Gross et al , 2012 and critical reflections of the second author who has grown up in the Kilombero Valley and now lives there as a young father and an anthropologist. Based on this interest, eight focus group discussions (FGDs) were organised in April 2009.…”
Section: Methodsmentioning
confidence: 99%